Eliminating female genital multilation : an interagency statement OHCHR, UNAIDS, UNDP, UNECA, UNESCO, UNFPA, UNHCR, UNICEF, UNIFEM, WHO (WHO GenevaCH, 2008)
Highlights the wide recognition of the human rights and legal dimensions of the problem and provides current data on the prevalence of female genital mutilation. Summarizes findings from research on the reasons why the practice continues as well as recent research on its damaging effects on the health of women, girls and newborn babies. Describes the elements needed, for both working towards complete abandonment of female genital mutilation, and caring for those who have suffered, and continue to suffer, from its consequences.
Keywords: CIRCUMCISION